(untitled) (Journal of Medical & Health Sciences Review, 2025)
Background: Measles is a serious and highly contagious viral disease that continues to affect people around the world, especially in areas with low vaccination rates. Although a safe and effective vaccine is available, outbreaks still happen, often because of poor awareness and false beliefs. Nursing students, as future health educators, need to have correct and clear knowledge about measles and how to prevent it. Aim: This study aimed to check how much nursing students know about measles and its vaccine, and to see if a short educational session could improve their knowledge. Methodology: A one-group pre-test and post-test design was used. The study was done at Albiruni College of Nursing, Hyderabad. A total of 66 undergraduate nursing students were selected through convenience sampling. An adapted questionnaire was used to collect data before and after the educational session. The results were analyzed using SPSS version 27, and a paired t-test was used to compare the scores. Results: The results showed a clear improvement in knowledge after the session. The average pre-test score was 8.863 (SD =2.44034), and the average post-test score was 11.590 (SD = 1.98837). The difference in scores was 2.7, with a p-value less than 0.001, which means the improvement was statistically significant and results are reliable. Conclusion: The study shows that short educational sessions can help improve nursing students’ knowledge about measles and its vaccine. Adding such sessions to nursing training can support students in becoming better vaccine educators and public health advocates.